DAMPAK WABAH PENYAKIT MULUT DAN KUKU (PMK) TERHADAP PRODUKSI SUSU DAN PENDAPATAN PETERNAK SAPI PERAH RAKYAT DI BOYOLALI: THE EFFECT OF FOOT AND MOUTH DISEASE (FMD) ON MILK PRODUCTION AND INCOME OF SMALLHOLDER DAIRY FARMERS IN BOYOLALI - Purwadi, Purwadi; Prasetyo, Aris Budi (Tropical Animal Science, 2024)
Foot and mouth disease (FMD) which attacks cattle (ruminants) in several regions in Indonesia, especially Boyolali, will directly impact the production, distribution, trade processes and affect the socio-economic activities of the community. Boyolali as a milk production center which has major livestock potential is also affected by this condition, especially smallholder dairy farmers, namely small farmers with a population of under 10 heads. This condition is very vulnerable to their socio-economic conditions. This research aims to determine the effect of the FMD outbreak on milk production and economic income at the smallholder farmer level. The results of this research can then be used as a basis for efforts to handle the outbreak, appropriate and measurable recovery efforts to maintain the economic resilience of smallholder dairy farmers in Boyolali to avoid bankruptcy. This research was carried out using a survey method in 6 milk producing sub-districts in the Boyolali region. Sampling was taken using purposive sampling based on ownership of dairy livestock under 10 heads among smallholder farmers. The research results showed that 99% of dairy farmers whose livestock were affected by FMD experienced a decrease in production by an average of 55%. Farmers must increase maintenance expenditures for treatment by an average of 33% of normal production costs. The average income of smallholder dairy farmers has decreased by 75%. Some extreme cases experienced by breeders include livestock deaths and 5% of livestock having to be culled, and breeders switching professions other than farming. The conclusion of this research is that PMK containers reduce the productivity of people's dairy cattle and affect the resilience of people's dairy farming businesses.